Application of bacillus megaterium for subclinical mastitis in cows - Yaroslav Tytukh (Scientific Route OÜ, 2021)
The problem of treatment of subclinical mastitis often arises after calving, especially in cows of the first lactation. The paper presents the results of the therapeutic effect of Bacillus megaterium in subclinical mastitis in cows.